2019
DOI: 10.1097/wnp.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Reliability of V-Wave Responses in the Soleus Muscle

Abstract: Purpose: The V wave is an electrophysiologic variant of the H reflex that is evoked with supramaximal stimulus intensity. In this study, we explored whether the between-day reliability of V-wave normalized amplitude varies as a function of the number of intrasession measurement trials. We also determined whether the reliability of the V wave improves after the exclusion of the initial testing trials. Methods: Eighteen healthy, young participants (10 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Testing was performed as reported in previous research (Mendonca et al., 2019). All assessments were made on the participants’ right lower limb, using a Biodex System 3 Pro isokinetic dynamometer (Biodex Medical System 3).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Testing was performed as reported in previous research (Mendonca et al., 2019). All assessments were made on the participants’ right lower limb, using a Biodex System 3 Pro isokinetic dynamometer (Biodex Medical System 3).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to exert their maximum force as fast and hard as possible and subsequently were allowed to rest for 60 s between trials. This protocol is highly reliable for torque measurements during a plantarflexor MVC (the intraclass correlation coefficient and 95% confidence interval of standard error of the measurement corresponding to 0.99 and 2.86, respectively) (Mendonca et al., 2019). The highest peak torque value obtained during plantarflexion was used to determine the individual torque output compatible with 10% MVC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2021, 11, 105 2 of 19 as N20 and N30, significantly decreased after cervical spinal manipulation in a relatively healthy population [12][13][14]. These early cortical SEP peaks are thought to represent the arrival of the afferent signals at the primary somatosensory cortex and early sensorimotor integration, respectively [15,16]. Interestingly, in a chronic stroke population, who are known to have a reduced amplitude of early SEP peaks [17], a recent study showed an increase in N30 SEP peak amplitude following chiropractic care [18].…”
Section: Introductionmentioning
confidence: 99%